2020
DOI: 10.1038/s41523-020-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting DCIS and invasive breast cancer by subtype suggests basal-like DCIS as distinct lesions

Abstract: Ductal carcinoma in situ (DCIS) is a non-invasive type of breast cancer with highly variable potential of becoming invasive and affecting mortality. Currently, many patients with DCIS are overtreated due to the lack of specific biomarkers that distinguish low risk lesions from those with a higher risk of progression. In this study, we analyzed 57 pure DCIS and 313 invasive breast cancers (IBC) from different patients. Three levels of genomic data were obtained; gene expression, DNA methylation, and DNA copy nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
6
23
0
Order By: Relevance
“…To assess how well DCIS aligned with the PAM50 classification, we evaluated the correlation of each DCIS tumor to the centroid of its assigned subtype and compared the correlations against those observed in 1109 IBCs from The Cancer Genome Atlas (TCGA; Figure 3A ). The median correlation (Spearman’s like DCIS samples was significantly lower than basal-like IBC samples (median IBC = 0.75; median DCIS = 0.38; P Bonferroni = 8.01x10; Wilcoxon rank sum test), as previously shown (Bergholtz et al, 2020). Significantly decreased correlation was also observed for luminal A (median IBC = 0.60; median DCIS = 0.50; P Bonferroni = 3.13x10) and normal-like subtypes (median IBC = 0.60; median DCIS = 0.49; P Bonferroni = 6.21x10).…”
Section: Resultssupporting
confidence: 84%
“…To assess how well DCIS aligned with the PAM50 classification, we evaluated the correlation of each DCIS tumor to the centroid of its assigned subtype and compared the correlations against those observed in 1109 IBCs from The Cancer Genome Atlas (TCGA; Figure 3A ). The median correlation (Spearman’s like DCIS samples was significantly lower than basal-like IBC samples (median IBC = 0.75; median DCIS = 0.38; P Bonferroni = 8.01x10; Wilcoxon rank sum test), as previously shown (Bergholtz et al, 2020). Significantly decreased correlation was also observed for luminal A (median IBC = 0.60; median DCIS = 0.50; P Bonferroni = 3.13x10) and normal-like subtypes (median IBC = 0.60; median DCIS = 0.49; P Bonferroni = 6.21x10).…”
Section: Resultssupporting
confidence: 84%
“…A major proportion of breast cancer samples are Luminal A, and this is also the case in the training cohort. We have previously shown that Luminal A DCIS and IBC are highly similar at a molecular level, while basal-like DCIS differ substantially from basal-like IBC (Bergholtz et al, 2020). Stratification by subtype prior to creating the models could yield different results and identify genes and biological processes relevant within each subtype, but this approach would, in our high-dimensional analysis, be limited due to rather low sample size of the current cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…As a model training data, we used multi-omics molecular and genomic profiles combined from three patient cohorts, Oslo2, Uppsala, and Milan ( Muggerud et al, 2010 ; Fleischer et al, 2014 ; Lesurf et al, 2016 ; Aure et al, 2017 ; Bergholtz et al, 2020 ). Each patient cohort contains three levels of omics data from gene expression microarrays, DNA methylation, and DNA copy number.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations